2006
DOI: 10.1093/ndt/gfl368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anaesthesia on fluid and solute transport in a C57BL6 mouse model of peritoneal dialysis

Abstract: Ketamine anaesthesia in the mouse decreases PA values for glucose and mannitol when used as osmotic agents in PD solutions. The decrease in transperitoneal transport for these osmotic agents increases the final volume of fluid which can be obtained from the peritoneal cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…General anesthesia with halothane in sheep significantly decreases the appearance of intraperitoneal macromolecular tracer in caudal mediastinal and thoracic duct lymph vessels (33). Recent peritoneal transport studies with short dwells in ketamine-anesthetized mice demonstrated significantly higher drained volumes compared to conscious mice (34). This observation was explained by direct effects of ketamine anesthesia on glucose metabolism and on serum glucose clearance (35).…”
Section: Discussionmentioning
confidence: 99%
“…General anesthesia with halothane in sheep significantly decreases the appearance of intraperitoneal macromolecular tracer in caudal mediastinal and thoracic duct lymph vessels (33). Recent peritoneal transport studies with short dwells in ketamine-anesthetized mice demonstrated significantly higher drained volumes compared to conscious mice (34). This observation was explained by direct effects of ketamine anesthesia on glucose metabolism and on serum glucose clearance (35).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the method chosen for anesthesia might influence the outcome of blood testing. Isoflurane anesthesia, for example, has been shown to cause impaired insulin secretion and glucose tolerance (Tanaka et al, ), and ketamine also seems to have effects on glucose metabolism (Shin et al, ). Methods that are associated with muscle injuries (blood vessel puncture in situ, heart puncture, submandibular vein puncture) can result in altered values of several parameters (e.g., muscle enzyme activities) measured in the sample.…”
Section: Commentarymentioning
confidence: 99%
“…Regarding peritonitis, many investigators have administered antibiotics in order to prevent infections, an intervention that has been proven successful and simultaneously not leading to morphological and function changes in the peritoneum (Mortier et al, 2003 ; Choi et al, 2006 ). Finally, the use of anesthesia when handling animals has been related to changes in the peritoneum kinetics, probably through a direct reduction of the lymphatic drainage (Tran et al, 1993 ) and an increase of ultrafiltration and decrease of the absorption rates from the peritoneal membrane (Shin et al, 2006 ).…”
mentioning
confidence: 99%